2013
DOI: 10.1002/pola.26692
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated polymerizable phosphonium salts from PH3: Surface properties of photopolymerized films

Abstract: An array of highly fluorinated polymerizable phosphonium salts (HFPPS) were synthesized from PH3 and utilized in UV‐curable formulations. Inclusion of these salts at very low loading (0.1–1 wt %) into hexanediol diacrylate (HDDA) resulted in hydrophobic surfaces. The water repellency was achieved with short C4F9 fluorocarbon appendages in the monomer as opposed to the bioaccumulative C8F17 appended polymers. The physical properties of these new monomers were also characterized. The molecular architecture of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
24
2
Order By: Relevance
“…27 By tuning the chemical structure of the phosphonium monomer, counterion, and cross-linker, it has been possible to readily tune properties such as coating hardness, hydrophobicity, swellability, and ion exchange rate. [28][29][30] The deposition of gold nanoclusters through ion exchange was also explored. 31 To the best of our knowledge, there are only two prior reports of SIPNs incorporating polyphosphoniums.…”
Section: Introductionmentioning
confidence: 99%
“…27 By tuning the chemical structure of the phosphonium monomer, counterion, and cross-linker, it has been possible to readily tune properties such as coating hardness, hydrophobicity, swellability, and ion exchange rate. [28][29][30] The deposition of gold nanoclusters through ion exchange was also explored. 31 To the best of our knowledge, there are only two prior reports of SIPNs incorporating polyphosphoniums.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, FILs are defined as ILs with fluorous tags equal to or longer than four carbon atoms (distinct from mere fluoro-containing ILs based on bis(trifluoromethylsulfonyl)imide, trifluoromethanesulfonate, hexafluorophosphate or tetrafluoroborate anions). Research on FILs has been reported in few works and has mainly focused on their synthesis and characterization,58 and their application as catalysts,9,10 lubricants,11 electrolytes for electricity storage and solar or fuel cells,12 as well as in materials 13. The use of FILs enables us to take unique advantages of both IL and FIL compounds: (i) highly fluorinated compounds, with outstanding chemical and biological inertness; and (ii) ionic liquids, with tuneable solvent quality, vanishing vapour pressure and greater potential.…”
Section: Introductionmentioning
confidence: 99%
“…The contact angles with water for PFP ·Br and PFP ·NTf 2 were correspondingly high at 63 and 76°, respectively. These contact angles with water are significantly lower than those achieved by the aforementioned fluorinated phosphonium polymers reported by Ragogna and coworkers (up to 101°) . Despite their ionic nature, however, the critical surface energies of PFP ·Br and PFP ·NTf 2 are significantly lower than those of familiar polymers such as polystyrene (γ c = 34 mJ m −2 ), poly(methyl methacrylate) (γ c = 37.5 mJ m −2 ) and polyethylene terephthalate (γ c = 39 mJ m −2 ) and on par with the values for well‐known hydrophobic polymers like poly(vinylene fluoride) (25 mJ m −1 ) and polydimethylsiloxane (23 mJ m −1 ) …”
Section: Resultsmentioning
confidence: 55%
“…Some low surface energy phosphonium polymers and salts have already been investigated. Ragogna and coworkers have prepared photopolymerizable tetraalkylphosphonium salts, cleverly designed to incorporate C 4 F 9 units rather than longer perfluoroalkyl chains that are persistent ecological threats . Despite the ionic backbone constituents, photopolymerized coatings of these fluorinated phosphonium polymers are quite hydrophobic, attaining water contact angles of up to 101 °C (cf.…”
Section: Introductionmentioning
confidence: 99%